National biodiversity and ecosystem assessments for conservation impact: Uptake and lessons learnt from the South African experience - Jessica M. da Silva; Colleen L. Seymour; Linda R. Harris; Lara van Niekerk; Anisha Dayaram; Amanda Driver; Thapelo Kgomo; Sediqa Khatieb; Samukelisiwe T. Msweli; Kerry Sink; Ntakadzeni Tshidada; Lize von Staden; et al. (Ambio, 2026)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

A short-interval longitudinal study of associations between psychological distress and hippocampal grey matter in early adolescence - Amanda Boyes; Jacob M. Levenstein; Larisa T. McLoughlin; Christina Driver; Lia Mills; Jim Lagopoulos; Daniel F. Hermens (Brain Imaging and Behavior, 2024)
This study of Australian adolescents ( N = 88, 12-13-years-old) investigated the relationship between hippocampal grey matter volume (GMV) and self-reported psychological distress (K10) at four timepoints, across 12 months. Participants were divided into two groups; those who had K10 scores between 10 and 15 for all four timepoints were categorised as “low distress” (i.e., control group; n = 38), while participants who had K10 scores of 16 or higher at least once over the year were categorised as “moderate-high distress” ( n = 50). Associations were tested by GEE fitting of GMV and K10 measures at the same time point, and in the preceding and subsequent timepoints. Analyses revealed smaller preceding left GMV and larger preceding right GMV were associated with higher subsequent K10 scores in the “moderate-high distress” group. This was not observed in the control group. In contrast, the control group showed significant co-occurring associations (i.e., at the same TP) between GMV and K10 scores. The “moderate-high distress” group experienced greater variability in distress. These results suggest that GMV development in early adolescence is differently associated with psychological distress for those who experience “moderate-high distress” at some point over the year, compared to controls. These findings offer a novel way to utilise short-interval, multiple time-point longitudinal data to explore changes in volume and experience of psychological distress in early adolescents. The results suggest hippocampal volume in early adolescence may be linked to fluctuations in psychological distress.

Compensatory responses to increased mechanical abnormalities in COPD during sleep - Nicolle J. Domnik; Devin B. Phillips; Matthew D. James; Grace A. Ayoo; Sarah M. Taylor; Robin E. Scheeren; Amanda T. Di Luch; Kathryn M. Milne; Sandra G. Vincent; Amany F. Elbehairy; Sophie J. Crinion; Helen S. Driver; et al. (European Journal of Applied Physiology, 2022)

Practical actions for applied systematic conservation planning - Emily A. Botts; Genevieve Pence; Stephen Holness; Kerry Sink; Andrew Skowno; Amanda Driver; Linda R. Harris; Philip Desmet; Boyd Escott; Mervyn Lötter; Jeanne Nel; Tammy Smith; et al. (Conservation Biology, 2019)
Systematic conservation planning is intended to inform spatially explicit decision making. Doing so requires that it be integrated into complex regulatory and governance processes, and there are limited instances where this has been achieved effectively. South Africa is a global leader in the application of conservation plans, the outputs of which are widely used for spatial planning and decision making in many spheres of government. We aimed to determine how conservation planning in the country progressed from theory to implementation, and to identify practical actions that enabled this transition, by assessing temporal trends in the characteristics of conservation plans (1990–2017, n = 94). Since 2010 conservation planning has entered an operational period characterized by government leadership of plans, administrative rather than ecological planning domains, decreasing size of planning units, increasing emphasis on end‐user products, and scheduled revision of plans. Key actions that enabled this progression include transitioning leadership of plans from scientists to practitioners, building capacity within implementing agencies, creating opportunities to integrate plans in legislative processes, establishing a strong community of practice, adopting implementation‐focused methods, and balancing standardization with innovation. Learning from this model will allow other countries, particularly those with a similar megadiverse, developing context, to operationalize conservation planning into spatial planning and decision making.

Knowledge co‐production and boundary work to promote implementation of conservation plans - Jeanne L. Nel; Dirk J. Roux; Amanda Driver; Liesl Hill; Ashton C. Maherry; Kate Snaddon; Chantel R. Petersen; Lindie B. Smith‐Adao; Heidi Van Deventer; Belinda Reyers (Conservation Biology, 2016)
Knowledge co‐production and boundary work offer planners a new frame for critically designing a social process that fosters collaborative implementation of resulting plans. Knowledge co‐production involves stakeholders from diverse knowledge systems working iteratively toward common vision and action. Boundary work is a means of creating permeable knowledge boundaries that satisfy the needs of multiple social groups while guarding the functional integrity of contributing knowledge systems. Resulting products are boundary objects of mutual interest that maintain coherence across all knowledge boundaries. We examined how knowledge co‐production and boundary work can bridge the gap between planning and implementation and promote cross‐sectoral cooperation. We applied these concepts to well‐established stages in regional conservation planning within a national scale conservation planning project aimed at identifying areas for conserving rivers and wetlands of South Africa and developing an institutional environment for promoting their conservation. Knowledge co‐production occurred iteratively over 4 years in interactive stake‐holder workshops that included co‐development of national freshwater conservation goals and spatial data on freshwater biodiversity and local conservation feasibility; translation of goals into quantitative inputs that were used in Marxan to select draft priority conservation areas; review of draft priority areas; and packaging of resulting map products into an atlas and implementation manual to promote application of the priority area maps in 37 different decision‐making contexts. Knowledge co‐production stimulated dialogue and negotiation and built capacity for multi‐scale implementation beyond the project. The resulting maps and information integrated diverse knowledge types of over 450 stakeholders and represented >1000 years of collective experience. The maps provided a consistent national source of information on priority conservation areas for rivers and wetlands and have been applied in 25 of the 37 use contexts since their launch just over 3 years ago. When framed as a knowledge co‐production process supported by boundary work, regional conservation plans can be developed into valuable boundary objects that offer a tangible tool for multi‐agency cooperation around conservation. Our work provides practical guidance for promoting uptake of conservation science and contributes to an evidence base on how conservation efforts can be improved .

Designing Systematic Conservation Assessments that Promote Effective Implementation: Best Practice from South Africa - ANDREW T. KNIGHT; AMANDA DRIVER; RICHARD M. COWLING; KRISTAL MAZE; PHILIP G. DESMET; AMANDA T. LOMBARD; MATHIEU ROUGET; MARK A. BOTHA; ANDRE F. BOSHOFF; J. GUY CASTLEY; PETER S. GOODMAN; KATHY MACKINNON; et al. (Conservation Biology, 2006)
Systematic conservation assessment and conservation planning are two distinct fields of conservation science often confused as one and the same. Systematic conservation assessment is the technical, often computer‐based, identification of priority areas for conservation. Conservation planning is composed of a systematic conservation assessment coupled with processes for development of an implementation strategy and stakeholder collaboration. The peer‐reviewed conservation biology literature abounds with studies analyzing the performance of assessments (e.g., area‐selection techniques). This information alone, however, can never deliver effective conservation action; it informs conservation planning. Examples of how to translate systematic assessment outputs into knowledge and then use them for “doing” conservation are rare. South Africa has received generous international and domestic funding for regional conservation planning since the mid‐1990s. We reviewed eight South African conservation planning processes and identified key ingredients of best practice for undertaking systematic conservation assessments in a way that facilitates implementing conservation action. These key ingredients include the design of conservation planning processes, skills for conservation assessment teams, collaboration with stakeholders, and interpretation and mainstreaming of products (e.g., maps) for stakeholders. Social learning institutions are critical to the successful operationalization of assessments within broader conservation planning processes and should include not only conservation planners but also diverse interest groups, including rural landowners, politicians, and government employees.

Nature Conservation Requires More than a Passion for Species - RICHARD M. COWLING; ANDREW T. KNIGHT; DANIEL P. FAITH; SIMON FERRIER; AMANDA T. LOMBARD; AMANDA DRIVER; MATHIEU ROUGET; KRISTAL MAZE; PHILIP G. DESMET (Conservation Biology, 2004)